Translation Analysis of Noun Phrases in I Wonder Why: Kangaroos Have Pouches and Other Questions About Baby Animals - Frandini Eris Yudianti (Media Antartika Indonesia, 2025)
This study focuses on analyzing the translation techniques of noun phrases and their translation qualityi n the book I Wonder Why: Kangaroos Have Pouches and Other Questions About Baby Animals. The method usedi s descriptive qualitative. The data sources consisted of the English version of the book as the source text (SL)a nd the Indonesian version as the target text (TL). The data analysis technique refers to the theory of translation techniques by Molina and Albir (2002) and the translation quality assessment model by Nababan et al. (2012).The results show that 14 translation techniques were used, with the most dominant technique being establishede quivalence. Established equivalence is used to adjust the context for easier understanding by child readers. The evaluation findings indicate that the translation of noun phrases in this book is of high quality. This indicates that, in general, the translation conveys meaning accurately, is acceptable within Indonesian linguistic norms, and is easily understood by the target readers. This study concludes that choosing the right translation technique significantly influences the quality of the translation, especially in children's texts, which require simplicity of language while maintaining accuracy of meaning. These findings can be a reference for translators in understanding the translation strategies of noun phrases, especially in the children's book genre